Literature Review of Job Description: Meta-analysis - Switasarra, Adelia Veneska; Astanti, Ririn Diar (Universitas Atma Jaya Yogyakarta, 2021)
A job description document is a formal document that exists in the organization that usually has a formal social structure. Whether it is a small-scale organization to a large-scale organization, every formal organization usually has this document. The study presented in this paper tries to present the summary of the research related to the job description document. In the previous research, there is less attention has been given to explore the role of a job description in the various aspects of decision making in the company. Therefore, the importance and the role of the job description to the company, especially in supporting decision-making in the company, is explored in this study. In this study, we reviewed 43 papers published between 2001 and 2021. Several aspects related to job description such as 1) Definition of the job description; 2) Development of job descriptions; and 3) Benefits of job descriptions based on four reviewed papers are explained. The selected articles are taken from the article database engine: Emerald Insight, Semantic Scholar, Proquest, Science Direct, Elsevier, Springer Link with the keyword